School Radio and Literacy: Possibilities for the 5th year of elementary school (Revista Contexto & Educação, 2023)
This article aims to present some reflections about school radio in the teaching of children in the 5th year of elementary school. For that, we discussed educommunication, then the creation of a school radio. next we discussed the issue of technical development of radio in the school environment. Ahead, we see the issues of reading, writing and literacy and, to conclude, we highlight the benefits of school radio. The main authors used in the research were: Baltar (2012), Consani (2015), Orozco Gómez (2014), Martín-Barbero (2000), Ausubel (1968), Freinet (1969), Bruner (1964, 1997), Pietri ( 2009), Freire (2019) and Vygotsky (2007, 2008). The methodology has a qualitative approach, with descriptive objectives and with bibliographic and documentary methods. The main result of the study is the discussion of the possibility of implementing a radio in the school, with the function of improving issues of literacy, reading, text interpretation, writing, among others.